Polymorphisms of Interleukin-1 Beta and Interleukin-17Alpha Genes Are Associated With Restless Legs Syndrome. (April 2014) - Hennessy, Mary Dawn; Zak, Rochelle S.; Gay, Caryl L.; Pullinger, Clive R.; Lee, Kathryn A.; Aouizerat, Bradley E.
Objective: Dopamine, iron, and inflammatory pathways are considered important to the development of restless legs syndrome (RLS). Recent genetic studies support involvement of dopamine and iron; however, cytokine gene variation in the inflammatory component remains unexplored. A recent study reported a high prevalence of RLS among HIV-infected adults. We estimate occurrence of RLS in an ethnically diverse sample of HIV-infected adults and examine differences in demographic factors, clinical characteristics, and biomarkers relating to dopamine, iron, and inflammation between adults with and without RLS symptoms. Design: A prospective longitudinal study aimed at identifying biomarkers of RLS symptom experience among HIV-infected adults. Method: 316 HIV-positive adults were evaluated using International RLS Study Group criteria. Genes were chosen for hypothesized relationships to dopamine ( NOS1, NOS2 ), iron ( HFE ) or inflammation-mediated by cytokine genes (interferon [ IFN ], interleukin [ IL ], nuclear factor kappa-B [ NFKB ], and tumor necrosis factor alpha [ TNFA ]). Results: Similar to general population estimates, 11% of the sample met all four RLS diagnostic criteria. Controlling for race, gender, and hemoglobin, carrying two copies of the minor allele for IL1B rs1143643, rs1143634, or rs1143633 or carrying the minor allele for IL17A rs8193036 was associated with increased likelihood of meeting RLS diagnostic criteria. Conclusion: This study provides preliminary evidence of a genetic association between IL1B and IL17A genes and RLS.